The Relationship Between The Intensity Of The Five Times Of Prayer To The Stress Of The Elderly In Pekauman Village - Muhammad Anwari; Meti Agustini; Agung Wibowo (Jurnal EduHealth, 2023)
According to the social ministry, the number of older people in Indonesia was more than 10% of the population in 2020. Currently, the population in Indonesia reached 269.9 million people. The total population aged over 60 years reached 28.7 million people. It means more than 10.6% of total resident in Indonesia is elderly. Carry on age is a period in which all people hope will undergo calm, peaceful, and prosperous life. Will but various problems in life which whack carry on age throughout his life, like lonely and hopelessness because of the loss of a spouse and relatives, as well as a physical decline, loss of professional consequence age already carry on and loss of social roles that can trigger stress in the elderly (Azizah, 2011). Use a method correlational with the cross-sectional approach. The population is elderly, which is at in Ward Pekaman amount 4,732 people elderly. Processing and analysis of data done with computerized using the spearman rank statistical test at a significant brick of 0.05. Based on the test, sperm rho obtained mark sig. (2-tailed) as big 0.000 (<0.05), it can be concluded that the variable intensity of the five daily prayers has a positive relationship with the variable stress level. With a mark Correlation coefficient negative value of -0.675. The Correlation Coefficient value is -0.675, in concludes the level connection second variable has a strong connection.